Studying on creation of hybridomas producing monoclonal antibody specific for progesteron - Trang, Nguyen Thi; Cu, Nguyen Thi; Phuong, Do Thi; Thao, Do Thi (Academia Journal of Biology, 2012)
The progesterone highest level is reached on the 21st and 22nd days of pregnancy. The concentrations of progesterone in milk and serum can be quantitatived. This concentration changes by time and is used as indicators of pregnancy or diseases in cattle. To quantity the amount of progesterone in milk or serum, using monoclonal antibody is very feasible. In our study, we were successful in fusion between myeloma SP2/0-Ag14 and the lymphoid B isolated from spleen of the mouse that were immunized by P3-Al at the dose of 500 mg/mouse/time as the most effective concentration. By using the limiting dilution method, we cloned and selected the 2 clones of hybridomas - MCAPr1 and MCAPr5 which were able to produce specific monoclonal antibody against progesterone. To check the specificity of achieved monoclonal antibodies, the supernatants collected from culturing hybridomas were tested with others steroids which is progesterone similar structures such as estradiol, testosterone and corticosterone. Without any cross reaction, the clone MCAPr1 is selected for further culture at the larger scale in mice. From 6/10 experiment mice, we collected 45 ml of ascite fluid. The purified monoclonal antibody gained from this ascite fluid is saved at the -80oC for developing the quantitative progesterone kit in future